PERUBAHAN BERAT BADAN ASEPTOR KB SUNTIK 3 BULAN DI PUSKESMAS KOTA KARANG: SURVEI ANALITIK - Gladeva Yugi Antari; Herliana Herliana; Rahmah Fitria (JOMIS (Journal of Midwifery Science), 2024)
The increase in side effects associated with the 3-month injectable contraceptive method is consistent with the number of people choosing to use this approach. One of the potential adverse effects of using 3-month injectable birth control is changes in body weight. Maternal health is not affected by this adverse effect, although it may cause 3-month contraceptive acceptors to switch methods or stop using contraception altogether. This research aims to understand the changes in weight gain of birth control acceptors over 3 months. The research method used is a correlational analytical survey with a cross-sectional approach. The sampling technique used total sampling with 29 respondents from March to April 2024. Research was conducted at the Karang City Health Center using primary and secondary data using methods such as observation sheets, questionnaires, and measuring the actual body weight of respondents. The results of this study showed that the majority of respondents experienced weight gain of 69% with a weight gain of ≥ 5 kg amounting to 9 people (31.1%), 3-4 kilograms amounting to 6 people (20.7%), and 1-2 kg by 5 people (17.2%).